2019
DOI: 10.1103/physrevb.100.075146
|View full text |Cite
|
Sign up to set email alerts
|

Charge-transfer effect in hard x-ray1sand2pphotoemission spectra:LDA+DMFTand cluster-model analysis

Abstract: We study 1s and 2p hard x-ray photoemission spectra (XPS) in a series of late transition metal oxides: Fe2O3 (3d 5 ), FeTiO3 (3d 6 ), CoO (3d 7 ) and NiO (3d 8 ). The experimental spectra are analyzed with two theoretical approaches: MO6 cluster model and local density approximation (LDA) + dynamical mean-field theory (DMFT). Owing to the absence of the core-valence multiplets and spin-orbit coupling, 1s XPS is found to be a sensitive probe of chemical bonding and nonlocal charge-transfer screening, providing … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 60 publications
1
47
0
Order By: Relevance
“…3def show the hybridization intensities V 2 (ε). The intensities around −8 to −2 eV (−2 to 4 eV) represent the hybridization with O 2p (Co 3d) states though explicit decomposition of contributing states in the continuum bath is impossible [51]. Despite the similar LS valence spectra in LiCoO 2 and LaCoO 3 , we find a clear difference in V 2 (ε) for the e g orbital between the two.…”
Section: Cobaltitesmentioning
confidence: 75%
“…3def show the hybridization intensities V 2 (ε). The intensities around −8 to −2 eV (−2 to 4 eV) represent the hybridization with O 2p (Co 3d) states though explicit decomposition of contributing states in the continuum bath is impossible [51]. Despite the similar LS valence spectra in LiCoO 2 and LaCoO 3 , we find a clear difference in V 2 (ε) for the e g orbital between the two.…”
Section: Cobaltitesmentioning
confidence: 75%
“…The core-level Ni 2p XPS spectrum of np-NiFeP displays three peaks with binding energies of 852.8, 856.0, and 861.6 eV assigned to Ni 3 P, Ni oxide or hydroxide, and relevant satellite peak, respectively ( Supplementary Fig. 11a) 20,38 . Meanwhile, two peaks with binding energies located at 706.5 and 712.8 eV in core-level Fe 2p XPS spectrum of np-NiFeP are ascribed to Fe 3 P and Fe oxide ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Yu et al [12] observed a shoulder B (∼ 856.5 eV) in the main line. Unlike A, the peak B is absent in the cluster-model spectra [14,29] and thus can be ascribed to NLS [12]. The sensitivity of the relative intensity of A and B to ∆ dp can be used locate its value to the interval 4.9-5.9 eV.…”
Section: Comparison To Experimental X-ray Spectroscopiesmentioning
confidence: 99%
“…In this paper, we use the local-density approximation (LDA) + dynamical mean-field theory (DMFT) [24][25][26] to calculate XPS, XAS and RIXS spectra [16,[27][28][29][30] of undoped infinite-layer nickelates. By comparison with the available experimental data we identify the most appropriate the CT energy and use it for classification within the Zaanen-Sawatzky-Allen scheme [10].…”
Section: Introductionmentioning
confidence: 99%